Evaluation of mist flow characteristic and performance in Minimum Quantity Lubrication (MQL) machining - Abd Rahim, Erween; Dorairaju, Hemarani (ScienceDirect, 2018)
Minimum Quantity Lubrication (MQL) is an alternative method to supply the cutting fluid in the formation of mist. MQL has proven to reduce machining cost and increase machining performance. The effectiveness and the working principle of MQL are still questionable with very few explanations provided. The present study is conducted to investigate the performance of MQL technique with different combination of spray and machining parameters. The Phase Doppler Anemometry (PDA) was used to characterize the lubricant spray under different input pressure for various nozzle outlet diameter of 2.5 mm (OD25) and 3.0 mm (OD30). This device can measure the amount of droplet and size. From these results, the distance of the nozzle to the cutting tip can be estimated. The turning performance in terms of cutting force and cutting temperature was evaluated under three levels of cutting speed and two levels of feed rate and at a constant depth of cut. The result shows that the most suitable mist flow pattern during machining was the largest spray cone angle supplied under 0.4 MPa input air pressure. In addition, significant reduction of cutting force and cutting temperature were obtained when using OD30 nozzle at the nozzle distances of 6–9 mm and the input air pressure of 0.4 MPa.